The Frequency and the Significance of TNF-α+CD19+ B-cell Population in Lymph Nodes of Patients with Squamous Cell Carcinoma of Head and Neck - Marzieh Norouzian; Fereshteh Mehdipour; Mohammad Javad Ashraf; Bijan Khademi; Abbas Ghaderi (Turkish Journal of Immunology)
Objective: B-cells can contribute to the suppression or progression of the tumor growth through the secretion of various cytokines. In this study, the relevance of B-cell cytokine production to the outcome variables in patients having squamous cell carcinoma (SCC) of the head and neck was studied. Materials and Methods: Thirty-six draining lymph nodes from untreated patients with tongue and larynx SCC were stimulated with CpG, recombinant CD40L and phorbol-12-myristate-13-acetate/ionomycin and analyzed by flow cytometry for the frequency of B-cell subsets based on interleukin (IL)-10 and tumor necrosis factor-alpha (TNF-α) cytokine production. Results: It was indicated that patients with uninvolved lymph nodes and low stage of the disease had an increased percentage of TNF-α+CD19+ B-cells (p=0.006 and p=0.041, respectively), whereas the frequency of IL-10+CD19+ B-cells showed an increasing trend in tumor-draining lymph nodes (TDLNs) of patients with grade 2+3 compared to grade 1 (p=0.054). Conclusion: Collectively, TNF-α-producing B-cells in TDLNs has been reported to be associated with good prognosticators in patients with SCC of head and neck that might have a positive role in immunity to SCC of head and neck.